David Hyun and architectural hybridity: first architect in the history of Korean immigration to America - Myengsoo Seo; Sujin Kim (Journal of Asian Architecture and Building Engineering, 2025)
This study focuses on David Hyun, the first registered Korean-American architect, and his architecture, which expressed the hybridity of East Asian ethnicity and architectural modernism in the late-twentieth-century urban environment of Los Angeles, California. Hyun was the son of a figure pivotal in promulgating Korea’s independence movement to the world during the Japanese colonial period. Hyun and his family immigrated to and settled in Hawaii in 1924. He later moved to Los Angeles, where he took night classes in architecture at the University of Southern California. Earning his architectural license in 1950, Hyun became the first 1.5-generation Korean immigrant to become a registered architect in the United States. He expressed cultural identity through his design works while engaging in various social activities as a leader of the Los Angeles Korean community. This study explores Hyun’s family background and examines his identity and practice as a Korean-American architect through his architectural and urban projects from the 1950s to the 1990s, including the Japanese Village Plaza, Korea City Master Plan, and Hyun Residence. Understanding Hyun and his architecture will hopefully contribute to research on the Korean diaspora across America and the world.